ANALISIS DAYA MINAT PENGUNJUNG TERHADAP EKOWISATA AIR TERJUN TEMBURUN KECAMATAN SIANTAN KABUPATEN KEPULAUAN ANAMBAS PROVINSI KEPULAUAN RIAU - Defrizal, Defrizal; Yoza, Defri; Oktorini, Yossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Indonesia has the potential of megabiodiversity because it has the most completely in the world’s biodiversity. Many potentials of tourism scattered through out indonesia archipelago which can be calculated fairly gobal appeal. One of the districts located in kepulauan Riau Province is kepulauan Anambas regency. Kepulauan Anambas Regency has natural forest and potential of nature ecotourism in the form of temburun waterfall flowing directly into the sea as the greatest potential in Anambas Regency as tourism attraction. This study aims to know the leisure of visitors to Temburun Waterfall Kepulauan Anambas Regency Kepulauan Riau Province and analyze the condition on infrastructure in Temburun waterfall Kepulauan Anambas Regency in kepulauan Riau province. This study using observation, quitionnaire and literature study. The result showed that visitor’s leisure in ecotourism Temburun waterfall Anambas regency relatively high with percentage of 92% of the 100% visitors who visited temburun waterfall and the infrastructure is something that influence each other and can not be separated by the sustainablity of tourism activities, for the state of infrastructure at the site of Temburun waterfall is quite good.Keywords : Ecotourism, Temburun Waterfall, Kepulauan Anambas